Hybrid event bed character and distribution linked to turbidite system sub‐environments: The North Apennine Gottero Sandstone (north‐west Italy). Issue 1 (3rd July 2017) - Fonnesu, Marco; Felletti, Fabrizio; Haughton, Peter D. W.; Patacci, Marco; McCaffrey, William D.
Abstract: This study documents the character and occurrence of hybrid event beds (HEBs) deposited across a range of deep‐water sub‐environments in the Cretaceous–Palaeocene Gottero system, north‐west Italy. Detailed fieldwork (>5200 m of sedimentary logs) has shown that hybrid event beds are most abundant in the distal confined basin‐plain domain (>31% of total thickness). In more proximal sectors, hybrid event beds occur within outer‐fan and mid‐fan lobes (up to 15% of total thickness), whereas they are not observed in the inner‐fan channelized area. Six hybrid event bed types (HEB‐1 to HEB‐6) were differentiated mainly on basis of the texture of their muddier and chaotic central division (H3). The confined basin‐plain sector is dominated by thick (maximum 9·57 m; average 2·15 m) and tabular hybrid event beds (HEB‐1 to HEB‐4). Their H3 division can include very large substrate slabs, evidence of extensive auto‐injection and clast break‐up, and abundant mudstone clasts set in a sandy matrix (dispersed clay ca 20%). These beds are thought to have been generated by highly energetic flows capable of delaminating the sea floor locally, and carrying large rip‐up clasts for relatively short distances before arresting. The unconfined lobes of the mid‐fan sector are dominated by thinner (average 0·38 m) hybrid event beds (HEB‐5 and HEB‐6). Their H3 divisions are characterized by floating mudstone clasts and clay‐enriched matrices (dispersed clay >25%) with hydraulically fractionated components (mica, organic matter and clay flocs). These hybrid event beds are thought to have been deposited by less energetic flows that underwent early turbulence damping following incorporation of mud at proximal locations and by segregation during transport. Although there is a tendency to look to external factors to account for hybrid event bed development, systems like the Gottero imply that intrabasinal factors can also be important; specifically, the type of substrate available (muddy or sandy) and where and how erosion is achieved across the system producing specific hybrid event bed expressions and facies tracts.